Striatal Overexpression of ΔJunD Resets L-DOPA-Induced Dyskinesia in a Primate Model of Parkinson Disease - Berton, Olivier; Guigoni, Céline; Li, Qin; Bioulac, Bernard H.; Aubert, Incarnation; Gross, Christian E.; DiLeone, Ralph J.; Nestler, Eric J.; Bezard, Erwan (Biological psychiatry (1969), 2009)
Involuntary movements, or dyskinesia, represent a debilitating complication of dopamine replacement therapy for Parkinson disease (PD). The transcription factor ΔFosB accumulates in the denervated striatum and dimerizes primarily with JunD upon repeated L-3,4-dihydroxyphenylalanine (L-DOPA) administration. Previous studies in rodents have shown that striatal ΔFosB levels accurately predict dyskinesia severity and indicate that this transcription factor may play a causal role in the dyskinesia sensitization process. We asked whether the correlation previously established in rodents extends to the best nonhuman primate model of PD, the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-lesioned macaque. We used western blotting and quantitative polymerase chain reaction (PCR) to compare ΔFosB protein and messenger RNA (mRNA) levels across two subpopulations of macaques with differential dyskinesia severity. Second, we tested the causal implication of ΔFosB in this primate model. Serotype 2 adeno-associated virus (AAV2) vectors were used to overexpress, within the motor striatum, either ΔFosB or ΔJunD, a truncated variant of JunD lacking a transactivation domain and therefore acting as a dominant negative inhibitor of ΔFosB. A linear relationship was observed between endogenous striatal levels of ΔFosB and the severity of dyskinesia in Parkinsonian macaques treated with L-DOPA. Viral overexpression of ΔFosB did not alter dyskinesia severity in animals previously rendered dyskinetic, whereas the overexpression of ΔJunD dramatically dropped the severity of this side effect of L-DOPA without altering the antiparkinsonian activity of the treatment. These results establish a mechanism of dyskinesia induction and maintenance by L-DOPA and validate a strategy, with strong translational potential, to deprime the L-DOPA–treated brain.